2013
DOI: 10.1007/s10495-013-0882-y
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 induces apoptosis of chronic myelogenous leukemia cells via dual activation of BIM and BID and overcomes various types of resistance to tyrosine kinase inhibitors

Abstract: PP2A activator FTY720 has been shown to possess the anti-leukemic activity for chronic myelogenous leukemia (CML), however, the cell killing mechanism underlying its anti-leukemic activity has remained to be verified. We investigated the precise mechanisms underlying the apoptosis induction by FTY720, especially focusing on the roles of BH3-only proteins, and the therapeutic potency of FTY720 for CML. Enforced expression of either BCL2 or the dominant-negative protein of FADD (FADD.DN) partly protected CML cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…14). Besides its use in relapsing multiple sclerosis patients for immunosuppression, FTY720 was also shown to induce apoptosis of various neoplastic cells, including solid tumors (15), acute lymphoblastic leukemia (16), and chronic myelogenous leukemia (17) and MM (18). FTY720 is reportedly cytotoxic to cancer cells by inducing both caspase-dependent and caspase-independent apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…14). Besides its use in relapsing multiple sclerosis patients for immunosuppression, FTY720 was also shown to induce apoptosis of various neoplastic cells, including solid tumors (15), acute lymphoblastic leukemia (16), and chronic myelogenous leukemia (17) and MM (18). FTY720 is reportedly cytotoxic to cancer cells by inducing both caspase-dependent and caspase-independent apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…FTY720 is an S1PR modulators and immunosuppressor for the treatment of multiple sclerosis. Notably, recent studies show that FTY720 also induces anticancer activity in several cancer models through S1PR-independent signaling pathways that are distinct from the well-known immunosuppressive activity [39, 40]. Therefore, the development of anticancer agents without S1PR effect can be free from immunosuppression.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that both metformin and FTY720 exerted their antitumor effects via at least partly affecting the levels of Bcl-2 proteins [28,29]. Therefore, we asked whether the combination of metformin and FTY720 could affect the levels of Bcl-2 proteins.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 97%